2021
DOI: 10.1002/ana.26212
|View full text |Cite
|
Sign up to set email alerts
|

Seizures after Ischemic Stroke: A Matched Multicenter Study

Abstract: The purpose of this study was to identify risk factors for acute symptomatic seizures and post-stroke epilepsy after acute ischemic stroke and evaluate the effects of reperfusion treatment. Methods: We assessed the risk factors for post-stroke seizures using logistic or Cox regression in a multicenter study, including adults from 8 European referral centers with neuroimaging-confirmed ischemic stroke. We compared the risk of post-stroke seizures between participants with or without reperfusion treatment follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 53 publications
4
53
3
Order By: Relevance
“…When these areas are damaged, a patient exhibits symptoms of seizure and dyskinesia as our patient did [ 3 5 ]. When brain MRI shows high signal intensity on DWI and low signal intensity on the ADC map, it mostly suggests acute ischemic stroke and about 6% of the patients experience post-stroke seizures [ 6 ]. A study of 3050 stroke patients reported that the incidence of caudate nucleus stroke was 1% of all patients and only 12% of them showed bilateral involvement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…When these areas are damaged, a patient exhibits symptoms of seizure and dyskinesia as our patient did [ 3 5 ]. When brain MRI shows high signal intensity on DWI and low signal intensity on the ADC map, it mostly suggests acute ischemic stroke and about 6% of the patients experience post-stroke seizures [ 6 ]. A study of 3050 stroke patients reported that the incidence of caudate nucleus stroke was 1% of all patients and only 12% of them showed bilateral involvement [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 The study by Ferreira-Atuesta et al reviewed here attempts to provide a definitive answer to this question using multicenter data and skillful statistical analysis. 7 They included 4229 adults with ischemic stroke, without prior epilepsy history, from 8 centers in 6 European countries. Of note, a sub-cohort of this study population was used for devising SeLECT score, a prognostic model to predict PSE.…”
Section: Commentarymentioning
confidence: 99%
“…In search of imaging biomarkers predicting the risk of poststroke seizures, a significant association between the incidence of PSE 2 years after the occurrence of hemorrhagic transformation post ischemic stroke in patients who underwent endovascular revascularization therapy was found (17.9% compared with 4.0%, p = 0.001; Thevathasan et al, 2018). In a recent study no impact of reperfusion techniques on the development of PSE was found (Ferreira-Atuesta et al, 2021).…”
Section: Post-stroke Epilepsymentioning
confidence: 99%
“…However, all patients who develop a single seizure more than 7 days after a stroke are classified as suffering from PSE as they have a 71.5% increased risk of developing further seizures within the next 10 years (Hesdorffer et al, 2009 ) and hence fall into the category of epilepsy according to the International League against Epilepsy (Fisher et al, 2014 ). Numbers of patients developing PSE vary due to different cohorts regarding the length of follow-up, stroke etiology, or varying definitions of early and RSS, but generally range from 3 to 25% (Galovic et al, 2018 , 2021 ; Feyissa et al, 2019 ; Xu, 2019 ; Ferreira-Atuesta et al, 2021 ). Risk factors for PSE include strokes with cortical involvement, stroke severity, young age (below 65 years), or ASS (Galovic et al, 2018 ; Feyissa et al, 2019 ; Zelano et al, 2020 ; Ferreira-Atuesta et al, 2021 ).…”
Section: Post-stroke Epilepsymentioning
confidence: 99%
See 1 more Smart Citation